Additive manufactured polyamide foams with periodic grid as templates for the production of functional coated carbon-bonded alumina foam filters. Issue 1 (January 2019) - Herdering, Andreas; Abendroth, Martin; Gehre, Patrick; Hubálková, Jana; Aneziris, Christos G.
Abstract: For the industrial production of metal melt filters, the replica technique is established since several decades. The polyurethane foams used as templates show a rather random structure with several defects which are transferred into the final filter structure after the replication. In order to generate filters with periodic structure and low amount of defects, a periodic foam model was used and open cell foams were produced by selective laser sintering of aged polyamide 12 (PA12). The PA12 foams were then used as sacrificial templates for the replica technique in the production route of Al2 O3 -C filters with functional coatings based on a cold sprayed Al2 O3 -C coating or a flame sprayed coating based on Al2 O3 . The differences in geometry between the computer-generated model foam, the sacrificial PA12 foam, the foam after carbonization, and the additional functionalized filters with the cold and hot coating were analyzed by computed tomography. Based on CT-data isosurfaces of the foams were generated to virtualize and distinguish the differences. Preliminary mechanical tests showed a higher cold crushing strength for the filters coated via flame-spray technique than the cold coating.